2014
DOI: 10.1111/jdi.12202
|View full text |Cite
|
Sign up to set email alerts
|

Increasing risk of diabetes mellitus according to liver function alterations in electronic workers

Abstract: Aims/IntroductionWe sought to determine the association between change in fasting plasma glucose (FPG) and levels of liver enzymes, such as aspartate transaminase, alanine transaminase and gamma-glutamyltransferase, from health examinations.Materials and MethodsA total of 9,393 health screen examinees with no evidence of viral hepatitis, liver diseases, abnormal liver function and diabetes in their past disease history were enrolled in the present study. All the participants underwent three health examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The high cholesterol level may be attributed to the presence of hypertension for diabetic conditions which however may be contributory factor in the prevalence of dyslipidemia in type 2 DM. This result agrees with the reports of Harris (2005) and Kyoungho et al (2014), who reported that high cholesterol presence in plasma of diabetic experimental animals treated with plant extract confirms the rise in blood pressure for animals that are diabetic. (Han et al, 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The high cholesterol level may be attributed to the presence of hypertension for diabetic conditions which however may be contributory factor in the prevalence of dyslipidemia in type 2 DM. This result agrees with the reports of Harris (2005) and Kyoungho et al (2014), who reported that high cholesterol presence in plasma of diabetic experimental animals treated with plant extract confirms the rise in blood pressure for animals that are diabetic. (Han et al, 2012).…”
Section: Resultssupporting
confidence: 93%
“…ALT showed significance (p<0.05) decrease for Group V while AST and ALP were not statistically significant for Group I to group IV. The result of ALT, ALP and ALP for Group I to Group V were within safe limits (Kyoungho et al, 2014;Harris, 2005).…”
Section: Resultsmentioning
confidence: 66%
“…It has been revealed by previous epidemiological studies that impaired liver function (evaluated by increased activity of liver enzyme, for example, alanine aminotransferase) is associated with progression of metabolic disorders. [1,2] Previous prospective studies demonstrates that Insulin resistance (IR) contributed to progression of many metabolic disorders like hypertension, central obesity, and dyslipidemia. [3][4][5] Recently, emerging researches also proposed that IR might also take a role in the development of impaired liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Liver enzymes, the most common markers of liver function in the clinic, include alanine transaminase (ALT) and aspartate aminotransferase (AST) 5–7. Related studies suggested that the elevation of liver enzymes levels was indicative of insulin sensitivity reduction, insulin resistance and type 2 diabetes development 8–10. Fasting plasma glucose (FPG) is the most commonly used index to monitor the occurrence of early type 2 diabetes, which is of great significance in the prevention of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Fasting plasma glucose (FPG) is the most commonly used index to monitor the occurrence of early type 2 diabetes, which is of great significance in the prevention of diabetes. Although previous studies have reported that liver enzymes levels were significantly associated with FPG levels,3 10 11 the evidence remained insufficient, because the reported results were inconsistent in terms of the population studied, such as populations from different regions and populations with different body mass indexes (BMIs). In addition, as we know, almost all related studies regarded BMI as only a covariate in the investigation of the relationship between liver enzymes levels and FPG levels in the general population, and few studies were conducted in Southern China.…”
Section: Introductionmentioning
confidence: 99%